Miscellaneous tapes - Grazier, Hobart E. 1917-1984.
Tapes Include : Chapel messages; Memorial services for him on 20 Aug.1984 and 29 Nov. 1984 ; lectures on Greek 3 ; and a symposium with A. Palma and L. McRae entitled Celebration 82.
Professor at VFCC 1964-1984.